Transient Modeling of NOX Reduction in Automobile Exhausts. (2015) - Lakshmanan, Niveda; Pratheeba, C.N.; Aghalayam, Preeti
Abstract: Regulations on automotive emissions are becoming increasingly stringent owing to the toxicity of gases like NOx, CO and unburned hydrocarbons. This brings the need for catalytic converters that convert the nitrogen oxides, CO and hydrocarbons to less harmful components. Steady state pseudo-homogeneous models for packed bed reactors have been developed earlier, taking into account the catalytic reduction of NO in the presence of CO. However, these models do not capture the transient behaviour of the reactor in real time systems. This project aims at developing a suitable transient model that is not computationally expensive but at the same time satisfactorily explains the behaviour of the converter at various operating conditions. The effect of the various operating parameters on the exit concentrations has also been studied. The major advantage of this system is that it takes into account the formation of N2 O as an undesirable by-product, during the reduction of NO. It also captures the selectivity of N2 formation under various conditions, and is expected to be useful in predicting start-up emissions of the vehicle.